Crossed fused Ectopic Kidney - A Case Report (TAJ: Journal of Teachers Association, 2009)
We present a case of crossed-fused ectopic left kidney in a young man who came with rightsidedabdominal pain for about 5 months. Crossed-fused ectopic kidney is often associated withother congenital anomalies, especially in the urinary tract. Our patient had two anomalies-ananomalous placement of renal pelvis (laterally in the orthotopic kidney), and a high up caecum,which was an asymptomatic associated gastrointestinal tract anomaly.doi: 10.3329/taj.v16i2.3889TAJ December 2003; Vol.16(2): 79-81